Political relations between the fatimid rule and theUmayyad state Andalus - Sajjad Hassan Al Noor; Prof.Dr Hamid Reda Shariat Madari; Prof.Dr Syid Nasser Mousavi (Journal of College of Education, 2024)
The study aims to explain the political relations between the Fatimid rule and the Umayyad state in Andalusia, where the Umayyad state provoked conflicts within Morocco and won the Berbers over to its side. Moreover, it made alliances with enemies of the Fatimid state, such as the Byzantine state. In contrast, the Fatimids tried to establish their presence in Andalusia by spreading the Ismaili doctrine. The forms of political conflict varied in many forms, including espionage between the interests of the two Fatimid states and the Umayyads of Andalusia, as well as the spiritual war in establishing an Islamic caliphate against the Fatimid state, and the interest of both parties in naval armament and terrorism of the opponent, which led to an increase in the conflict and Abd al-Rahman al-Umayyad’s control over the front Moroccan seaports and the win over of the sheikhs. The clans against the Fatimids. The hostile movements of the two conflicting parties made the Umayyad regime form an alliance front with the Islamic tribes hostile to the Fatimids and the internal Umayyad conflict in Andalusia against Shiism. Many debates emerged between the Fatimid and Umayyad caliphs, and each of the two states had special methods that it used in its conflict with the other state. History books included news about the conflict between the Fatimids and the Umayyads and the forms, causes, and results of this conflict. These relations later turned into military clashes. A study of the relations between the Fatimid rule and the Umayyad rule in Andalusia shows that these conflicts were based on a set of foundations, such as readiness to respond to any attempt to weaken their state, increase their influence, and establish strong diplomatic relations with other countries to ensure their stability and confront challenges. The research will shed light on the political relations between the Fatimid state and the Umayyad state, and study the methods followed by each of them in its political struggle with the other state.